1989
DOI: 10.1172/jci113877
|View full text |Cite
|
Sign up to set email alerts
|

Novel tool for the study of cholecystokinin-stimulated pancreatic enzyme secretion.

Abstract: The molecular events that mediate cholecystokinin (CCK)-

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
54
0

Year Published

1990
1990
2016
2016

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(55 citation statements)
references
References 14 publications
1
54
0
Order By: Relevance
“…This result confirms previous reports [8] and suggests a more complex activation process and/or signal transduction pathway as recently documented [31].…”
Section: Discussionsupporting
confidence: 93%
“…This result confirms previous reports [8] and suggests a more complex activation process and/or signal transduction pathway as recently documented [31].…”
Section: Discussionsupporting
confidence: 93%
“…It is well established that CCK-8 dose-dependently stimulates secretion of amylase from dispersed rat pancreatic acini, which reaches maximal secretion at 100 pM, and at supramaximal concentrations (i.e., 10 nM CCK-8) an inhibition of secretion from the maximal level is observed (3,8). In contrast to CCK, CCK-OPE is as efficacious a secretagogue but does not exhibit an inhibition of secretion at supramaximal doses (>0.1 µM) (8). We examined acini exposed to these CCK-8 stimulation protocols for the locations of Munc18c, syntaxin-4, and SNAP-23 by laser confocal microscopy.…”
Section: Resultsmentioning
confidence: 99%
“…The preparation of isolated rat acini was performed by a mechanical and enzymatic dissociation technique as we have previously described (8)(9)(10)(11). The acini were resuspended in oxygenated Krebs-Ringer-HEPES buffer, consisting of (in mM): 104 NaCl, 5 KCl, 1 KH 2 PO 4 , 1.2 MgCl 2 , 2 CaCl 2 , 0.2% (wt/vol) BSA, 0.01% (wt/vol) soybean trypsin inhibitor, 10 mM glucose, 25 mM HEPES/NaOH, pH 7.4, supplemented with MEM and glutamine.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…As regards receptor activation by JMV-180, although it has been observed that JMV-180 binding is insensitive to GTP [182] and that JMV-180 does not seem to promote activation of guanine-nucleotide-binding regulatory protein(s) on plasma membranes [177], other studies have documented the interaction of JMV-180 with two affinity classes of sites on rat /166, 1681 and mouse 11671 pancreatic acini. In addition, a recent study on digitonin-permeabilized acini has suggested the involvement of guanine-nucleotide-binding regulatory protein in JMV-180-stimulated secretion [ 181 1.…”
Section: Correlation Between Binding Data and Cck-a Receptor Functionmentioning
confidence: 99%